The transnational cult of Mount Wutai : historical and comparative perspectives - Andrews, Susan (Specialist in Buddhism and East Asian religions); Chen, Jinhua, 1966-; Guang, Kuan (Leiden ; Boston : Brill, 2021)
"The Transnational Cult of Mount Wutai explores the pan-East Asian significance of sacred Mount Wutai from the Northern Dynasties to the present day. Offering novel readings of comparatively familiar visual and textual sources and, in many cases, examining unstudied or understudied noncanonical materials, the papers collected here illuminate the roles that both local actors and individuals dwelling far beyond Mount Wutai's borders have played in its making and remaking as a holy place for more than fifteen hundred years. The work aims to contribute to our understanding of the ways that sacred geography is made and remade in new places and times"--
Flying Mañjuśrī and Moving Mount Wutai Towards the Xi Xia Period: As Seen from Dunhuang Caves -- Wei-Cheng Lin -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 12, 2021).
eBooks on EBSCOhost
Keywords: Mañjūśrī; Buddhism -- China -- Wutai Mountains -- History; Mañjuśrī (Buddhist deity) -- Cult -- China -- Wutai Mountains; Buddhist pilgrims and pilgrimages -- China -- Wutai Mountains; Sacred space -- China -- Wutai Mountains; Wutai Mountains (China) -- Religion -- History; Wutai Mountains (China) -- History; Wutai Mountains (China) -- Religion; Bouddhisme -- Chine -- Wutai Shan -- Histoire; Lieux sacrés -- Chine -- Wutai Shan; Wutai Shan (Chine) -- Religion; Wutai Shan (Chine) -- Histoire; Buddhism; Buddhist pilgrims and pilgrimages; Cults; Religion; Sacred space; China -- Wutai Mountains; History